2002
DOI: 10.1063/1.1486478
|View full text |Cite
|
Sign up to set email alerts
|

Laser diode structure for the generation of high-power picosecond optical pulses

Abstract: A laser diode structure is designed and tested that permits the generation of high-power (∼100 W) picosecond-range optical pulses. Direct current pumping is used with a current pulse duration of a few nanoseconds and a current amplitude of ∼105 A/cm2. The main distinguishing feature of the structure is separation of the electron injector (p–n junction) from the active region by a potential barrier. The optical gain in the active region is controlled by the transverse electric field, which is determined by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Gain switching of semiconductor lasers, known for their high efficiency, compactness, and ease of current pumping, is arguably the best way of producing such pulses [1], [2]. The gain switching regime has been subject to extensive theoretical (see, e.g., [3]- [5]) and experimental (see, e.g., [5]- [13]) studies for a long time. It has been found that in order to maximize both the peak power and the total energy of the optical pulse, the design of lasers for gain switching may need to be different from that used for CW applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gain switching of semiconductor lasers, known for their high efficiency, compactness, and ease of current pumping, is arguably the best way of producing such pulses [1], [2]. The gain switching regime has been subject to extensive theoretical (see, e.g., [3]- [5]) and experimental (see, e.g., [5]- [13]) studies for a long time. It has been found that in order to maximize both the peak power and the total energy of the optical pulse, the design of lasers for gain switching may need to be different from that used for CW applications.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that in order to maximize both the peak power and the total energy of the optical pulse, the design of lasers for gain switching may need to be different from that used for CW applications. A number of specialist gain-switched or combined gain-and Q-switched [11]- [13] laser designs have been suggested, and pulses with an energy >1 nJ have been demonstrated. Most of the earlier approaches used purpose-built ultrafast GaAs-based current pulse generators providing current pulses with an amplitude significantly exceeding 10 A.…”
Section: Introductionmentioning
confidence: 99%
“…. R 0 that it takes to charge the capacitor C 0 (see Fig.12) between two pulses, so that the repetition rate cannot be higher than f R m~[ (2)(3) . τ 0 ] -1 .…”
Section: Possible Bottlenecks For the Maximum Repetition Rate In Highmentioning
confidence: 99%
“…Laser diodes with direct current pumping are ideally suited for all these requirements, except that only a few techniques can provide high peak power (~10-100 W) in a single picosecond-range pulse [3][4][5] . All the possible candidates are widestripe picosecond laser diodes, which require pumping with high-current (~10 2 A) pulses of a duration of a few nanoseconds.…”
Section: Introductionmentioning
confidence: 99%
“…Practical applications which would benefit from the development of a high-speed semiconductor device of this kind are advanced radars with high single-shot resolution 1 , precise 3 D imaging 2 , laser tomography, time imaging spectroscopy, etc. It would also be fairly attractive to use this switch for feeding the recently suggested picosecond laser diodes 3 and others 4 . High-speed (ps-range) high voltage pulses could be used in electro-optical and electron beam shutters, streak-camera sweep modules, etc.…”
Section: Introductionmentioning
confidence: 99%